2023
DOI: 10.4132/jptm.2022.11.02
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease–associated intestinal fibrosis

Abstract: Fibrosis is characterized by a proliferation of fibroblasts and excessive extracellular matrix following chronic inflammation, and this replacement of organ tissue with fibrotic tissue causes a loss of function. Inflammatory bowel disease (IBD) is a chronic inflammation of the gastrointestinal tract, and intestinal fibrosis is common in IBD patients, resulting in several complications that require surgery, such as a stricture or penetration. This review describes the pathogenesis and various factors involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…This discovery offers an explanation for the rigidity and dilation of the distal pouch noticed during surgery, as well as the decrease in constipation rate after more than 3cm distal resection. Moreover, brosis is a consequence of chronic in ammation and the replacement of healthy organ tissue with brotic tissue leading to the loss of function [29]. The possible association between brosis and chronic in ammation in the rectal pouch was suggested by Berg et al in 2008 and con rmed by Bhatia et al who found the presence of chronic in ammatory in ltration in 18 out of 19 patients with brosis [8, 28].…”
Section: Discussionmentioning
confidence: 99%
“…This discovery offers an explanation for the rigidity and dilation of the distal pouch noticed during surgery, as well as the decrease in constipation rate after more than 3cm distal resection. Moreover, brosis is a consequence of chronic in ammation and the replacement of healthy organ tissue with brotic tissue leading to the loss of function [29]. The possible association between brosis and chronic in ammation in the rectal pouch was suggested by Berg et al in 2008 and con rmed by Bhatia et al who found the presence of chronic in ammatory in ltration in 18 out of 19 patients with brosis [8, 28].…”
Section: Discussionmentioning
confidence: 99%
“…EMT is also activated in inflammatory bowel diseases (IBDs) such as ulcerative colitis (UC) and Crohn’s disease (CD) [ 48 ]. In IBD patients, persistent intestinal inflammatory factors injure intestinal epithelial cells, determining reparative reactions that lead to the triggering of the EMT process and perpetuating a severe fibrotic condition [ 48 , 49 ].…”
Section: Role Of Emp/emt In Organ Fibrosismentioning
confidence: 99%
“…EMT is also activated in inflammatory bowel diseases (IBDs) such as ulcerative colitis (UC) and Crohn’s disease (CD) [ 48 ]. In IBD patients, persistent intestinal inflammatory factors injure intestinal epithelial cells, determining reparative reactions that lead to the triggering of the EMT process and perpetuating a severe fibrotic condition [ 48 , 49 ]. Confirming this, the presence of high levels of tumor necrosis factor-like ligand 1A (TL1A) in the intestinal specimens of patients with UC and CD has been detected, which represents a potent inducer of EMT in intestinal fibrosis.…”
Section: Role Of Emp/emt In Organ Fibrosismentioning
confidence: 99%
“…Chronic inflammation is recognized as a leading promoting factor of diseases including carcinogenesis [ 24 ], which continues to be the leading cause of mortality and disability around the world [ 25 , 26 , 27 , 28 ]. Tumour-promoting inflammation is recognised as an enabling hallmark of cancer [ 29 ].…”
Section: Polyacetylenes and Inflammationmentioning
confidence: 99%